Use cloudy App Builder in the learning process - M. V. Petrashenko (Academy of Cognitive and Natural Sciences, 2015)
On the basis of forms of interaction between the learning process is investigated using applications for mobile operating systems using cloud applications designers, presented the idea for this app. The main purpose - easy access to the site, library or materials discipline. The objective of the study is an analysis of the most appropriate sources of information for the student using the experimental method by selectively install on your smartphone or tablet. The object of research is the application for smartphone. Subject of research - the use of the application in the educational process. Results of the study - the creation of applications for smartphones. Conclusions: the use app allows you to combine the most relevant information and connect students and teachers in the learning process.